From Campaigns to Systems: Evaluating the Effectiveness of Indonesia’s One Village, One ECE - Cep Kiki Kusumah (The Journal of Indonesia Sustainable Development Planning, 2025)
Early childhood education (ECE) is a critical foundation for human capital development. This study evaluates Indonesia’s 2022 “One Village, One ECE” campaign, which aims to expand access to early childhood education. Using pooled cross-sectional, fixed-effects, and random-effects models on district-level data (2019-2024), we assess the policy's impact on gross enrollment rates (GER) for children aged 3–6 as a part of the proxy indicator SDG 4.2 (ECE) and a key foundation for achieving SDG 8 (Decent Work and Economic Growth). Findings indicate that local campaign commitment alone does not significantly increase enrollment. Instead, enrollment gains are driven by strategic factors: infrastructure expansion, local ECE budgets, and the Family Hope Program (PKH). We conclude that political commitment must be complemented by systemic implementation to achieve universal ECE access, so that a finding reflected in Indonesia’s relevant policy shift toward 13 years of compulsory education (1 year pre-primary and 12 years primary and secondary education).